Social Proximity, Information, and Incentives in Local Bank Lending - Wang, Junbo; Wang, Yun; Wu, Chunchi; Yang, Xiaoguang; Zhao, Lin (The Review of Corporate Finance Studies, 2024)
Abstract Exploring the role of social proximity in bank lending using a proprietary data set, we uncover evidence of a significant social proximity effect on private information acquisition. Local loan officers have better information to identify higher-quality borrowers through improved screening. This advantage is greater when firms have higher information asymmetry and lower ratings. Results suggest that sociocultural resources drive locals’ informational advantages and improve their lending performance. Importantly, we find that the social proximity advantage interacts with loan officer incentives. Strong evidence suggests that loan officers can be incentivized to use their social proximity advantage to make better loans. (JEL G12, G13) Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.